Republic of Armenia : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2019)
Armenia's fiscal transparency practices have benefitted from public financial management reforms over the last decade, and several planned reforms will bring further progress. Fiscal forecasts and budgets have become more forward looking and policy oriented, with the introduction of a medium-term expenditure framework (MTEF), improved fiscal objectives, and a performance budgeting system. Fiscal risk disclosure, though fragmented, has gradually improved, in particular, in macrofiscal risk assessment, and a PPP law is being drafted. The accrual accounting reform will significantly improve the coverage and quality of the budget execution reports and fiscal statistics that already provide timely and frequent information about the financial position of the government.